Sustaining the blue bounty: Fish food and nutrition security in Nigeria's evolving blue economy - Saba, Abdulwakil Olawale; Eyo, Victor Oscar; Elegbede, Isa Olalekan; Fakoya, Kafayat Adetoun; Ojewole, Akinloye Emmanuel; Dawodu, Fareed Olatunji; Adewale, Rashidat Adebola; Amal, Mohammad Noor Azmai (AIMS Press, 2024)
Fish is a key component of Nigeria's protein supply, making up about 40% of the nation's protein intake and considerably aiding in the achievement of the second Sustainable Development Goal of feeding the expanding population. Despite its importance, Nigeria's fish production and supply cannot keep up with demand. While total fish output has increased from 1,073,059 tonnes in 2014 to 1,169,000 tonnes in 2018 and is expected to reach 1,275,000 tonnes by 2030, there is a great supply gap. Fish production not only affects food security but also the national economy and employment. Notwithstanding, the fisheries sub-sector suffers several difficulties, such as poor management, a deficient fisheries policy, overfishing, diminishing catch, and a lack of technical know-how among fish growers and fishermen. Thus, exploring untapped aquaculture potential and managing small-scale fisheries effectively are necessary to close the gap between the demand for and supply of fish. The fish output situation can be improved by enforcing fisheries policy and regulations, increasing investments in ethical fisheries and aquaculture, and providing sufficient training for fish farmers and fisherfolk. To reduce waste associated with the limited number of fish now produced, post-harvest losses must also be addressed. By solving these issues and putting in place the necessary actions, Nigeria can increase its fish production, strengthen its food security, and accomplish the sustainable development goals in its evolving blue economy.